Knowledge, attitude and uptake of mammography among female health workers in two tertiary health facilities of Sokoto state, Nigeria - Raji, Mansur O; Adamu, Shehu P; Akinnibosun-Raji, Hafsat O; Raji, Hadija O; Ango, Umar M; Kaoje, Aminu U (International Journal Of Community Medicine And Public Health, 2021)
Background: Globally, breast cancer is the most common cancer in women and early detection remains the cornerstone of breast cancer control in terms of outcome and survival. Female health care workers, being frontline healthcare providers, often come in contact with patients and their relatives and can disseminate accurate mammography information. This study thus aimed to determine the knowledge, attitude and uptake of mammography among female health workers working in two tertiary health care facilities in Sokoto state, Nigeria. Methods: The study was cross sectional in nature. Using formula for estimating sample size for cross-sectional studies, a sample size of 209 was obtained. All female health care workers were eligible to participate in the study. Systematic sampling was used to recruit them into the study. A self-administered questionnaire was used for data collection. Data was subsequently entered into IBM statistical software package version 20. Descriptive and inferential analysis was performed All statistical tests were carried out using 2 tailed test with alpha set at 0.05. Results: Less than a fifth of the respondents knew the age screening mammography end if no breast problem is detected, less than half (44.4%) of the respondents knew how frequent a screening mammography be obtained after the age of 40 years. Less than a tenth (7.9%) of the respondents had ever had mammography done. Conclusions: Majority of our study participants had good overall mammography related knowledge, most of them demonstrated positive attitude towards mammography, the uptake of mammography in our study population was very low.